The Farm Labor Movement in the Midwest : Social Change and Adaptation among Migrant Farmworkers - Barger, W. K. (Walter Kenneth), 1941- (Book collections on Project MUSE., 1994)
The Farm Labor Movement in the Midwest will be of interest to a wide interdisciplinary audience, including Mexican American studies, sociology, psychology, political science, anthropology, labor history, and economics.